Activation of peroxydisulfate by nanoscale zero-valent iron for sulfamethoxazole removal in agricultural soil: Effect, mechanism and ecotoxicity. (May 2019) - Zhou, Zhou; Ma, Jun; Liu, Xitao; Lin, Chunye; Sun, Ke; Zhang, Huijuan; Li, Xiaowan; Fan, Guoxuan
Abstract: In this study, peroxydisulfate (PDS) was successfully activated by nanoscale zero-valent iron (nZVI) for the degradation of sulfamethoxazole (SMX, antibiotic frequently detected in the environment) in agricultural soils. The results indicated that the degradation of SMX was affected by the nZVI dose, the ratio of SMX/PDS, the ratio of soil/water and reaction temperature, and in cinnamon soils 87.6% of SMX degradation can be achieved within 4 h at 30 °C when the initial nZVI dose was 0.03 g g −1 soil, the molar ratio of SMX/PDS = 1/75 and the soil/water = 1/1. The results of radical scavenger experiments and electron spin resonance (ESR) tests showed that hydroxyl radical ( OH) was the dominant reactive species in this system. The ecotoxicity tests of the soil by germination test, luminescent bacteria experiment and enzyme activity test indicated that the ecotoxicity of soil after treatment was obviously lower than the contaminated soil. In addition, there was almost no effect on plant growth when compared with original soil. Furthermore, this system exhibited a great degradation capacity for SMX in different types of agricultural soils, and the degradation efficiencies of SMX in other four soils were 90.6% (yellow brown earths), 80.8% (brown earths), 86.5% (black soils) and 96.1% (red earths), respectively. This work provides an optional method for agricultural soil pollution control. Highlights: PDS/nZVI system exhibited excellent effect for SMX removal from agricultural soil. In the treated soil, the dominant radical was confirmed as hydroxyl radical. The contaminated soil after treatment by PDS/nZVI system showed lower ecotoxicity.